Pelatihan Komunikasi Efektif Tentang Pencegahan Bahaya Narkoba Bagi Sukarelawan Dalam Menyukseskan Program Sekolah Bersinar (Bersih Narkoba) - Susanti, Ari; Izzuddin, Ahmad (Universitas Muhammadiyah Jember, 2023)
This service is a follow-up to the results of previous research that discussed Therapeutic Communication in Drug Social Rehabilitation Clients at the Gennesa Banyuwangi Foundation. In a previous study, it was found that one of the clients at the Gennesa Foundation had been taking drugs since elementary school grade 5 types of alcohol and cigarettes. Starting from trial and error with the invitation of friends around him, then getting used to stealing and selling things in his house just to satisfy his addiction. Drugs have spread among children. Therefore, effective communication techniques are needed to socialize the dangers of drugs to children. This service is carried out by holding effective communication training for volunteers with the Training of Trainer (ToT) model which is attended by 25 students from various universities in Jember Regency. This devotion format is packaged in composition: 20% theoretical exposure, 20% discussion and 60% simulation. The material presented was socialization of the dangers of drugs, effective communication in the fight against drugs and simulations of effective communication techniques. The hope to be achieved from this service is that trained volunteers can be deployed in socializing the dangers of drugs to children in their neighborhoods and schools